Is Reading Impairment Associated with Enhanced Holistic Processing in Comparative Visual Search?. (7th October 2016) - Wang, Jiahui; Schneps, Matthew H.; Antonenko, Pavlo D.; Chen, Chen; Pomplun, Marc
Abstract : This study explores a proposition that individuals with dyslexia develop enhanced peripheral vision to process visual–spatial information holistically. Participants included 18 individuals diagnosed with dyslexia and 18 who were not. The experiment used a comparative visual search design consisting of two blocks of 72 trials. Each trial presented two halves of the display each comprising three kinds of shapes in three colours to be compared side‐by‐side. Participants performed a conjunctive search to ascertain whether the two halves were identical. In the first block, participants were provided no instruction regarding the visual–spatial processing strategy they were to employ. In the second block, participants were instructed to use a holistic processing strategy—to defocus their attention and perform the comparison by examining the whole screen at once. The results did not support the hypothesis associating dyslexia with talents for holistic visual processing. Using holistic processing strategy, both groups scored lower in accuracy and reacted faster, compared to the first block. Impaired readers consistently reacted more slowly and did not exhibit enhanced accuracy. Given the extant evidence of strengths for holistic visual processing in impaired readers, these findings are important because they suggest such strengths may be task dependent. Copyright © 2016 John Wiley & Sons, Ltd.